2013
DOI: 10.1159/000345418
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of Paraprotein to Platelet Receptors as a Cause of Platelet Dysfunction in Monoclonal Gammopathies

Abstract: The study included 48 untreated patients with monoclonal gammopathies (MG). Paraprotein was isolated from the serum of 10 patients with decreased platelet aggregation. Platelet aggregation was measured before and after the addition of the isolated paraprotein to platelet-rich plasma (PRP) from 10 healthy donors, in vitro. Expression of platelet von Willebrand factor (vWF) receptor glycoprotein (GP)Ib and platelet collagen receptor GPVI was determined by flow cytometry in the PRP of healthy donors before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
(20 reference statements)
2
12
0
Order By: Relevance
“…Binding of IgA to the platelet FcαRI receptor has also been demonstrated to stimulate release of pro‐inflammatory cytokines, interleukin (IL)‐1β and tissue factor 63 . The finding of PAIg in subsets of patients with SM/MM, and PAIg in patients with MGUS with relatively low paraprotein levels, supports reports that disease‐specific changes affect paraprotein specificity or aggregation to facilitate PAIg 60,64,65 . Various mechanisms for PAIg may be involved and could be assessed in future work.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Binding of IgA to the platelet FcαRI receptor has also been demonstrated to stimulate release of pro‐inflammatory cytokines, interleukin (IL)‐1β and tissue factor 63 . The finding of PAIg in subsets of patients with SM/MM, and PAIg in patients with MGUS with relatively low paraprotein levels, supports reports that disease‐specific changes affect paraprotein specificity or aggregation to facilitate PAIg 60,64,65 . Various mechanisms for PAIg may be involved and could be assessed in future work.…”
Section: Discussionmentioning
confidence: 55%
“…50 This may be attributed to blockade of specific surface receptors by paraproteins, hindering agonist-receptor interactions. 60 Paraprotein binding may also trigger receptor signalling that contributes to platelet hyperactivation. Our present finding of hyperactivation in these patients may involve Fc receptor signalling.…”
Section: Figmentioning
confidence: 99%
“…19,20 Although this method was questioned for a lack of sensitivity to detect certain types of platelet disorders (eg, secretion or granula defects), these defects are not typically found in MM. 7 In MM and PCD, interference of paraproteins with the platelet VWF receptor (GPIb, CD42b) and collagen binding sites (GPVI, CD36) 21,22 has been shown to cause a disturbed interplay of platelet cytoadhesive receptors and their ligands. In addition, paraproteins with specificity for GPIIIa have been found and resulted in a significant bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain drugs 9,10 and procedures 11,12 that can affect platelet function need to be considered in these complicated patients (Table 1), but removal of the paraprotein is generally effective in improving platelet function and helps in correcting the bleeding diathesis. Djunic et al 13 showed that paraproteins bind to specific platelet receptors such as the platelet vWF receptor GPIb and platelet collagen receptor GPVI (decreased CD42b and CD36 expression on flow cytometry, respectively. On addition of paraprotein to platelet-rich plasma from normal healthy donors), thereby affecting their function.…”
Section: Discussionmentioning
confidence: 99%
“…On addition of paraprotein to platelet-rich plasma from normal healthy donors), thereby affecting their function. 13 New generation instruments such as multiplate multiple electrode aggregrometry using whole blood impedancemetry allow multiple functional studies to be performed on platelets using agonists (such as ADP test, RISTO test, COL test among others) using the help of multiple channels on the analyzer. 14 In paraprotein associated aVWD, the laboratory reports will show a normal PT and prolonged APTT which corrects on mixing.…”
Section: Discussionmentioning
confidence: 99%